Pembelajaran Seni Musik Berbasis Game Online (Kajian Fenomenologis Pendidikan Common Ground) - Putra, Zakarias Aria Widyatama; Olendo, Yudhistira Oscar (Smart Education, 2024)
Abstract: Music learning in the 21st century combines the concepts of music theory and practice in the frame of creativity, critical thinking, collaboration, and communication, which are integrated in the digitalization era. It is necessary to investigate more deeply the learning of music in the digitalization era, especially online games, in terms of phenomena and literacy studies so that it can dismiss the negative stigma of the presence of online games on students. Various theories and research, such as literacy studies obtained as well as analyzing the phenomenon of learning music and online games, have an understanding that the construction of online games can be adapted into music teaching materials. It is hoped that the results of this phenomenon, that the music materials designed in online games can be adjusted at the education level (elementary, junior high, and high school) so that they can be remembered and increase the memory of music learning materials (common ground). Keywords: common ground; music learning; online games Abstrak: Pembelajaran seni musik di abad 21 menggabungkan konsep teori musik dan prak-tinya dalam bingkai kreativitas, berpikiri kritis, kolaborasi, dan komunikasi yang mana hal tersebut terintegrasi dalam era digitalisasi. Perlu diselediki lebih mendalam akan pembelajaran seni musik di era digitalisasi khususnya game online secara fenomena dan kajian literasinya, sehingga dapat menepis stigma negatif kehadiran game online pada peserta didik. Berbagai teori dan penelitian sebagai kajian literasi yang didapat serta analisis fenomena pembelajaran seni musik dan game online mendapatkan kesepahaman bahwa konstruksi game online dapat diadaptasi dalam materi ajar seni musik. Menjadi harapan akan hasil fenomena ini, bahwasanya materi-materi seni musik yang didesain dalam game online dapat disesuaikan pada jenjang pendidikan (SD, SMP, dan SMA) sehingga dapat dikenang dan meningkatkan daya ingat akan materi pembelajaran seni musik (common ground). Kata kunci: common ground; game online; pembelajaran seni musik